PENGALAMAN SARKOMA SINOVIAL DI RUMAH SAKIT HASAN SADIKIN, TERUTAMA PADA SARKOMA SINOVIAL BAHU KANAN - Isburhan, Mohamad Rizal; Rizki, Kiki Akhmad (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research was conducted at Hasan Sadikin Hospital by taking histopathological examination data from 2015 to 2018. There were 24 patients with distribution, 11 male patients and 13 female patients. Synovial sarcoma in the upper extremities was 9 patients and 15 patients in the lower extremities. Synovial sarcoma type is biphasic in 10 patients and monophasic in 14 patients. Reported male, 25 years with synovial sarcoma on the right shoulder. Physical examination of the patient revealed a lump with scar tissue with a soft tissue mass palpable with a size of 10x8x8cm, flat surface, springy consistency without pain. The patient underwent radiotherapy with a total of 60 gray radiation. The patient underwent wide excision under general anesthesia with the result of a tumor mass-free margin from postoperative histopathological examination. Patients are routinely controlled every 3 to 6 months to see any recurrences and metastases. Cases of synovial sarcoma are quite rare cases, a common primary soft tissue malignancy, often occurring in adolescents and young adults with the majority aged 15-40 years.